Berberis vulgaris fruit extract mitigated apoptosis in experimentally induced testicular ischemia and reperfusion injury in rats - Yigit, Serdar; Akgun, Sakir; Yesilyurt, Isa; Bitiktas, Soner; Taskin, Ergin; Alper Kahraman, Ali; Yayla, Muhammed; Kilicle, Pınar Aksu; Ali Bingol, Seyit; Ozdemir, Bengul; Akdogan, Gül Esma; Karagöz, Mehmet Ali (Frontiers in Pharmacology, 2025)
AimThe aim was to investigate the possible protective effect of Berberis vulgaris extract, which has anti-inflammatory and antioxidant properties, in the testes in an ischemia–reperfusion (IR) injury model by utilizing molecular, biochemical, histopathological, and immunohistochemical methods.MethodsA total of 56 male rats were divided in to 7 equal groups. Ischemia was induced by taking the testicles out of the scrotum and rotating them 720° and after 3 h reperfusion was induced. Berberis vulgaris extract was administered 3 h before ischemia. The reperfusion groups were treated by oral gavage 1 h before reperfusion. Following the 3-h reperfusion period, tissue and blood samples were collected.ResultsHistopathologically, H&E staining showed disruption in the seminiferous tubule structure in the ischemia and IR groups SOD levels decreased significantly in the IR group compared to the control group, whereas Berberis vulgaris did not change SOD levels following IR at 300 and 600 mg/kg doses. At the dose of 600 mg/kg, Berberis vulgaris significantly increased SOD levels compared to the ischemia group CAT activity was significantly higher in the BV300 and BV600 groups compared to the ischemia group. CAT activity was significantly lower in the IR group compared to the ischemia group (p < 0.001). When compared to the control group, the ischemia group had a roughly 3-fold increase in caspase-3 expression. In the IR group, this ratio was dramatically increased—roughly 5-fold. However, the antiapoptotic gene Bcl-2 expression was significantly decreased in both the ischemia and IR groups compared to the control group.ConclusionB. vulgaris plant extract may have a protective effect against testes IR injury. Further molecular studies are needed to clarify this protective effect.